Study of the mechanical properties of pipes used in irrigation networks in the Libyan market - Algoul, Salah (Libyan Journal of Science &Technology, 2022)
The variety in types and grades of Irrigation pipes make industry standards is more significant. These standards serve to identify each kind of Irrigation pipe, dimensions, workmanship, sustained, and pressure. The present work thus aims to study the mechanical properties of three types of pipes, which are used in irrigation networks (in the domestic Libyan market). The tensile strength, impact, and hardness tests were investigated. Based on the results obtained, the highest value for the hardness test was recorded by pipes manufactured in Libya (from pure raw material S1) 609. Meanwhile, the other pipes (S2, S3) registered 541 and 508 respectively. Pipes (S3) proved to be better in the impact test where it recorded 63.7KJ/m2.In contrast, the pipes (S1) showed 33.3 KJ/m2 and as expected, the recycled pipes (S2) have revealed the lowest value for the impact test 13.27KJ/m2.